Differences in Effect of High-Intensity Interval Training and Moderate-Intensity Continuous Training on Cardiorespiratory Fitness and Waist-to-Hip Ratio in Overweight Adolescents in Denpasar - Djuliana, Salsabila Fernanda; Luh Putu Ratna Sundari; Nur Basuki; I Putu Adiartha Griadhi; I Dewa Ayu Inten Dwi Primayanti; Indira Vidiari Juhanna (International Journal of Public Health Excellence (IJPHE), 2025)
Overweight has become a serious public health issue, as proven by the increasing morbidity and mortality rates in this population. Therefore, physical exercise interventions such as high-intensity interval training (HIIT) and moderate-intensity continuous training (MICT) are needed as training programs that can improve cardiorespiratory fitness (CRF) and reduce cardiometabolic risk. The aim of this study is to determine the differences in the effects of HIIT and MICT on CRF and the waist-to-hip ratio (WHR). This study used the randomized control group pretest-posttest design research method. The research sample included of 20 adolescents divided into two groups. Group 1 received the HIIT intervention, and Group 2 received the MICT intervention. CRF was assessed using the 20-meter shuttle run test (20m-SRT) also WHR. The mean test on CRF show that in group 1 (p<0.05) and group 2 (p<0.05) there are significant differences pre and post-test training. The Mann-Whitney U-test results show significant difference (p<0.05). Meanwhile, the WHR mean test results show that in group 1 (p<0.05) and group 2 (p<0.05) also has significant differences pre and post-test training. The Independent sample t-test results show no significant difference (p>0.05). This study concluded that HIIT is more effective than MICT in improving cardiorespiratory fitness. Thus, HIIT is as effective as MICT in reducing the waist-to-hip ratio of overweight adolescents.